Comparison of two echocardiography-based methods for evaluating pediatric left ventricular diastolic dysfunction - Xiang, Xue; Zhu, Xu; Zheng, Min; Tang, Yi (Frontiers in Pediatrics, 2023)
To investigate the consistency between the 2016 ASE/EACVI guidelinebased recommendation and the body surface area (BSA)-transformed Z value-based cut-off in the assessment of left ventricular diastolic function (LVDF) in children. Methods Clinical data of children with heart failure (HF) and those with a high risk of HF and those with a low risk of HF were collected from the Children's Hospital of Chongqing Medical University from March 2021 to October 2022. Mitral annular e' velocity, lateral E/e' ratio, left atrial volume index and peak tricuspid regurgitation velocity were detected by echocardiographyEchocardiography. The cut-off value recommended by the 2016 ASE/EACVI guidelines and the cut-off value based on the BSA-transformed Z value were used to evaluate LVDF. The consistency and difference of the two criteria were compared.Results A total of 132 children with HF, 189 with a high risk of HF, and 231 with a low risk of HF, were enrolled. The consistency of the two criteria in evaluating LVDF in children with HF and with a high risk of HF was moderate, with weighted kappa coefficients of 0.566 and 0.468, respectively (P<0.001). The positive rate of left ventricular diastolic dysfunction (LVDD) with Z value-based criteria (HF group was 23.5% and high-risk group was 8.5%) was higher than that with guideline-based criteria (HF group was 15.6% and high-risk group was 3.2%). In children with a low risk of HF, no case with LVDD was found. The consistency of the two criteria in grading the degree of LVDD was moderate, and the kappa coefficient was 0.522 (P=0.001). The degree of LVDD with Z value-based criteria was higher than that with guideline-based criteria (P=0.004).The Z value-based criteria used to evaluate LVDD in children with HF and in those with a high risk of HF may be more conducive to early identification of LVDD, thereby permitting the possibility of earlier early treatment intervention.